If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-11(2x+3)=18
We simplify the equation to the form, which is simple to understand
7-11(2x+3)=18
Reorder the terms in parentheses
7+(-22x-33)=18
Remove unnecessary parentheses
+7-22x-33=+18
We move all terms containing x to the left and all other terms to the right.
-22x=+18-7+33
We simplify left and right side of the equation.
-22x=+44
We divide both sides of the equation by -22 to get x.
x=-2
| x+37+x+4x-39=964 | | 3x+4-x=26 | | h(x)=3x^2-24x+53 | | x+x+17+3x=97 | | -2x+15=x+6 | | 24=5-(3-2x) | | 24=5-(3+2x) | | x-22=4x+2 | | n-17=-27 | | 3+2y-1=7y+20-3y | | n-17=27 | | x-6=2x+1 | | (4x+43)=(8x+7) | | x-6=2x*1 | | 2[p-2(p+1)]-1=8p+25 | | -6(3x-7)=21 | | 2[p-2p+2]-1=8p+25 | | 22=-2(x+6) | | 3mi=ft | | 80ft=yd | | x-3=2x+3 | | 3.1x-8.2=-0.2+7.1x | | -2x+28=2x+12 | | 4(x-5)=-2(x+9) | | -x-7=2x+2 | | 2x-12x+53=0 | | 4(b-1)=-4+4b+3 | | x+38=4x+14 | | x-4=2x+1 | | -6x=-60 | | -x-3=2x+6 | | x-1=2x+5 |